Taxonomic changes in the Neotropical wasp moths, Euchromiina and Ctenuchina (Lepidoptera, Erebidae, Arctiinae, Arctiini) relating to the fauna of Trinidad & Tobago, with descriptions of new species - Cock, Matthew J.w.; Laguerre, Michel (Zootaxa, 2022)
The following new species are described: Calonotos flemingi new species from Trinidad; Valvaminor jacerda new species from Trinidad and Venezuela. The following species are made subspecies new status: Calonotos tripunctata Druce, 1898 of C. aterrima (Sepp, 1847); Calonotos craneae Fleming, 1957 of Calonotos helymus (Cramer, 1775). The following subspecies is raised to species new status: Cosmosoma bolivarensis Klages, 1906 (formerly Cosmosoma achemon var. bolivarensis). The following are new combinations: Myrmecopsis kenedyae (Fleming, 1957) (Euchromiina) (formerly Pseudosphex kenedyae Ctenuchina); Valvaminor endoleuca (Druce, 1905) (formerly Mesothen endoleuca); Xanthyda beebei (Fleming, 1957) (formerly Pheia beebei); Eucerioides obliquifascia (Rothschild, 1912) (formerly Eucereon obliquifascia); Uranophora andrei (Rothschild, 1912) (formerly Ctenucha andrei). A lectotype is designated for Calonotos tiburtus trinidadensis Strand, 1915, which is a new synonym of Calonotos aterrima (Sepp, 1847). Aethria jacksoni Kaye 1925 is a new synonym of Aethria aner Hampson 1905.